The Impact of Accreditation on the Growth of Academic Libraries in Nigeria - Familusi, B. E.; Adetunla, G. B.O. (International Journal of Online and Distance Learning, 2016)
Purpose: The library being the most essential pillar of any academic institution needs utmost attention to avoid total collapse of the entire university community. The process of programmes accreditation in Nigerian universities is to ensure a uniform Maximum Academic Standards (MAS). To ensure that the process is meeting its set goals and objectives, this study examines the impact of accreditation on the growth of academic libraries in Nigeria. Methodology: The research adopts a descriptive survey design. A total enumeration technique was used to select 125 respondents as the sampled population. Questionnaire was used for data collection and analyzed using simple percentage. Results: The finding revealed that there is paucity of funds affecting the optimum performance of academic libraries in Nigeria; fund is not released until accreditation is approaching. Findings further revealed that accreditation exercise has been beneficial to the library in terms of increased library information resources and library face lift. The finding also revealed some of the challenges facing academic libraries in Nigeria. When there is no accreditation, the library faces poor attention and lack of fund from the university management which results to poor library services and no acquisition. Policy recommendation: Therefore, the study recommends that academic libraries in Nigeria should device a means of self-funding through Internally Generated Revenue (IGR) in form of bindery, internet access provision, reprographic services etc. Also, the university managements should continue to fund its library and release to time the statutory 10% total budget of the institution's recurrent expenditure.